NEW OPPORTUNITIES FOR OXYBUTININ APPLICATION AMONG CHILDREN WITH URINATION DISORDERS - S.N. Zorkin; S.A. Borisova; T.N. Gusarova ("Paediatrician" Publishers LLC, 2007)
The article gives the findings of M-cholinolytic oxybutinin hydrochloride (Driptane) application among children with urination disorders and enuresis caused by the hyperactivity of the urinary bladder. The researchers show efficiency and safety of the intravesical drug injection according to the elaborated methodology, which allowed for the improvement of the treatment results among children with a combined pathology of the upper urinary tracts and marked side effects in the event of the conventional oral therapy.Key words: urination disorders, enuresis, children, oxybutinin hydrochloride, hyperactivity of the urinary bladder.